The Influence Of Traveloka Media Exposure And Hotel Promotional Media On Consumers Decision To Stay At Hotel Horison Lampung - Ade Irma Pertiwi; Budhi Waskito; Noning Verawati (CV. Doki Course and Training, 2025)
The background of this research is based on changes in consumer behavior when choosing accommodation, where online platforms like Traveloka have become a primary source of information before making a booking. The method used is a quantitative approach with multiple linear regression analysis techniques. Data was obtained through surveys and analyzed using validity tests, reliability tests, descriptive statistics, and regression tests. The results of the study show that Traveloka ratings do not have a significant effect on the decision to stay, indicating that consumers tend to consider other factors such as price and location. On the other hand, Traveloka reviews were found to have a significant influence, reflecting the important role of customer reviews in shaping perceptions and building trust in the hotel. In addition, hotel promotional media also significantly influenced consumer decisions, where visual and interactive content through digital channels proved effective in attracting interest and creating an emotional connection with potential guests. These findings contribute to the development of digital marketing strategies in the hospitality industry, particularly in increasing occupancy rates and customer satisfaction at Hotel Horison Lampung